EDUKASI DAN PELATIHAN SENAM OTARIA SEBAGAI ASUHAN ESENSIAL PADA KELOMPOK IBU NIFAS DI WILAYAH KERJA PUSKESMAS KARANG INTAN 2 - Januarsih, Januarsih; Rita Kirana; Ahmad Rizani (Bajang Institute, 2024)
The experience of being a parent is not always pleasant, especially being a mother. The reality is that the responsibility of motherhood often causes conflict within a woman. A postpartum woman needs physical and psychological adaptation in the first weeks after giving birth. In the adaptation process, some women manage to adapt well but others do not manage to adjust and experience psychological disorders with various symptoms or a syndrome called Baby Blues Syndrome. One of the efforts to prevent the occurrence of baby blues is by doing physical activity. Physical activity in the form of postpartum exercises that can be done immediately after delivery with movements that increase every day according to the mother's ability. Postpartum exercises with regularity can accelerate the recovery of physiological and psychological health status after childbirth. The most important physiological health recovery is the acceleration of healing of the uterus, abdomen, and hip muscles that have been traumatized and accelerate the return of these parts to their normal form. Psychologically, postpartum exercises can increase the mother's ability to deal with stress and relax so as to reduce postpartum depression. Based on aesthetic or beauty assessment, postpartum exercises will improve the elasticity of muscles that have been stretched, maintain good posture, and restore body slimness